CryoWriter: a blotting free cryo-EM preparation system with a climate jet and cover-slip injector. (4th August 2022) - Rima, Luca; Zimmermann, Michael; Fränkl, Andri; Clairfeuille, Thomas; Lauer, Matthias; Engel, Andreas; Engel, Hans-Andreas; Braun, Thomas
Abstract : A microfluidic sample preparation method for TEM, which entirely avoids paper blotting and allows the passivation of the air–water interface during the preparation process, is presented. Abstract : Electron microscopy (EM) introduced a fast and lasting change to structural and cellular biology. However, the sample preparation is still the bottleneck in the cryogenic electron microscopy (cryo-EM) workflow. Classical specimen preparation methods employ a harsh paper-blotting step, and the protein particles are exposed to a damaging air–water interface. Therefore, improved preparation strategies are urgently needed. Here, we present an amended microfluidic sample preparation method, which entirely avoids paper blotting and allows the passivation of the air–water interface during the preparation process. First, a climate jet excludes oxygen from the sample environment and controls the preparation temperature by varying the relative humidity of the grid environment. Second, the integrated "coverslip injector" allows the modulation of the air–water interface of the thin sample layer with effector molecules. We will briefly discuss the climate jet's effect on the stability and dynamics of the sample thin films. Furthermore, we will address the coverslip injector and demonstrate significant improvement in the sample quality.